Comparison of Incision Types Used for Kidney Extraction in Laparoscopic Donor Nephrectomy: A Retrospective Study: Incision types for kidney extraction - Şahin, Selçuk; Özdemir, Osman; Ekşi, Mithat; Evren, İsmail and Karadağ, Serdar and Özlü, Deniz Noyan and Taşçı, Ali İhsan (Urology Journal, 2022)
Purpose: Laparoscopic donor nephrectomy (LDN) is the most commonly used method for kidney removal in kidney transplantation and, various incisions are used for kidney extraction. In this study, we aimed to compare the results of LDN operations using iliac fossa incision and Pfannenstiel incision. Material and Method: LDN cases performed in our institute between June 2016 and February 2020 were retrospectively analyzed. Patients with previous abdominal surgery, bleeding coagulation disorders, ectopic kidneys, and patients who were converted to perioperative open surgery were excluded. Demographic data of the patients, operation times, warm ischemia times, complications were recorded and the patients were divided into two groups according to incision types. Results: After the inclusion and exclusion criteria, 203 patients were included in the study. Iliac fossa incision was used in 65% of the patients and the Pfannenstiel incision was used in 35% of the patients to remove the donor’s kidney. There were no difference in age, body mass index, gender, and Charlson Comorbidity Index (CCI) scores between the two groups. Operation time and warm ischemia time were significantly longer in the Pfannenstiel group (p = 0.001 and p = 0.016 respectively). There was no significant difference between the two groups in terms of bleeding amount, length of hospital stay, need for narcotic analgesic, visual analog scale scores, and postoperative complications. Conclusion: Both types of incisions can be used successfully and safely for the extraction of the kidney in LDN. Although WIT and operation time has been observed to be longer when a Pfannenstiel incision is made, complications and analgesic use are not different between Pfannenstiel incisions and iliac fossa incisions.